Pemeriksaan TiLV (Tilapia Lake Virus) Pada Ikan Nila (Oreochromis niloticus) Budidaya - Fitria, Dina; Fathonah, Deffya; Afrianti, Rini; Turrohmah, Azizah; Mujaidiah; Destiana, Anggari Linda; Day, Dafzel; Astuti, Indri (PendIPA Journal of Science Education, 2025)
Nile Tilapia (Oreochromis niloticus) is highly sought after by Indonesian consumers and is one of the leading commodities cultivated in freshwater. However, tilapia farming still frequently encounters challenges that lead to a decline in production, one of which is infection by pathogens such as Tilapia Lake Virus (TiLV). TiLV can infect fish in waters with temperatures above 25°C, with mass mortality peaking at 30°C, reaching a 50% death rate. Proper handling and control measures are essential to manage TiLV outbreaks effectively. TiLV detection in fish can be conducted using the Polymerase Chain Reaction (PCR) method. PCR-based virus detection is a diagnostic technique that identifies the presence of viral genetic material with high specificity and accuracy. This study aimed to detect TiLV infection in farmed Nile tilapia. The procedures included sample collection, necropsy, organ fixation, RNA extraction, PCR amplification, electrophoresis, and gel documentation analysis. Based on the PCR results, Nile tilapia samples tested positive for TiLV infection, as indicated by the presence of a 250 bp DNA band in the gel documentation system, aligning with the TiLV positive marker. Among the three fish showing suspected TiLV symptoms, two (66.6%) were confirmed infected.